Budaya Kreatif dalam Konsep dan Pengembangan - Susanto, Eko (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
This study is an attempt to understand the concept of culture as a creative and cultural influence of external factors in fostering creativity. Culture is believed to be one of the aspects that can facilitate the growth of individual creativity. Creative culture as behavior, activity or way of life of a person or group of people embedded within it an element of novelty to life effective, communicative and refer to attitudes toward the social situation and the phenomenon of life. This study attempted to reveal the dominance of internal and external forces that encourage individual creativity. Of the 198 participants were high school students known that the external aspect dominates 63% as the force that drives one's creativity. Socializing creative culture from an early age is expected to facilitate the growth of creativity in the individual.